2006
DOI: 10.1007/s00384-006-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of STAT3 by antisense oligonucleotide in TNBS-induced murine colitis

Abstract: STAT3 activation may play an important role in the inflammatory process of TNBS-induced colitis, and inhibiting STAT3 activation during the early phase of the inflammatory response may have a beneficial effect on the colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Indeed, activation of these pathways has been described in conjunction with dextran sulfate sodium-induced colitis in mice and TNBS-induced colitis in rodents (Bai et al, 2007;Kretzmann et al, 2008;Youn et al, 2009;Fitzpatrick et al, 2011b). Moreover, we have reported that Vido inhibits activation of these intracellular signaling pathways in the mouse colon and murine splenocytes (Fitzpatrick et al, 2011b).…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, activation of these pathways has been described in conjunction with dextran sulfate sodium-induced colitis in mice and TNBS-induced colitis in rodents (Bai et al, 2007;Kretzmann et al, 2008;Youn et al, 2009;Fitzpatrick et al, 2011b). Moreover, we have reported that Vido inhibits activation of these intracellular signaling pathways in the mouse colon and murine splenocytes (Fitzpatrick et al, 2011b).…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, STAT-3 and pSTAT-3 levels also correlate with the histologic profile of experimental inflammation tissues [48, 49]; therefore STAT-3 seems to be a potential therapeutic target for ulcerative colitis. In previous work, Bai et al [50] studied the blockade of STAT-3 by antisense oligonucleotides in trinitrobenzenesulphonic acid-(TNBS-)induced murine colitis. As can be seen in our results, in noncolitic animals, only weak immunoreactivity was detected in the nucleus for pSTAT-3 (Figure 9(c)).…”
Section: Resultsmentioning
confidence: 99%
“…But, SA effectively controlled the activation of STAT3 in DSS‐induced mice (Figure ). STAT3 antisense oligonucleotide (Bai et al, ) or IL‐6 receptor‐mediated STAT3 activation blockade (Mitsuyama et al, ) was able to significantly enhance colonic inflammation in UC of murine models. Plant‐based natural agent has been previously reported to show protection against DSS‐induced UC by suppressing the activation of STAT3 (Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%